Sugarcane yield fertigation management with doses of N and inoculated with diazotrophic bacteria - Dellabiglia, William José; Gava, Glauber José De Castro; Arlanch, Adolfo Bergamo [UNESP]; Boas, Roberto Lyra Villas [UNESP]; Cantarella, Heitor; Rossetto, Raffaella (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
The objective of this study was to evaluate the efficiency of inoculation with diazotrophic bacteria and nitrogen fertilization on yield and technological quality of sugarcane (cane plant), in the following managements: irrigated by subsurface drip and rainfed. The experiment was conducted at Hélio de Moraes Research Unit, of IAC in the municipality of Jaú, SP, (22 ° 17 'S 48 ° 34' O, Rhodic). The variety of sugarcane was RB92579. The experimental design was randomized blocks, composed by factorial of two irrigation management systems: irrigated (I) and non-irrigated (NI); and two-inoculation managements: with inoculation (Inoc) and without inoculation (No inoc) with diazotrophic bacterias (BDs); and 4 availability levels of nitrogen (0, 70, 140 and 210 kg ha-1 de N), thus forming 16 treatments with 4 replications. The experiment lasted 365 days when then technological analysis was performed and determined sugarcane stalk yield (TCH) and sugar yield (TPH). The sugarcane raised its productivity with rising nitrogen levels. In irrigated treatments this increase was higher compared with non-irrigated treatments.
Produtividade de cana-de-açúcar fertirrigada com doses de N e inoculadas com bactérias diazotróficas
Keywords: Nitrogen biological fixation; Nitrogen fertilization; Saccharum spp.; Subsurface drip